Designing of a Magnetodielectric System in Hybrid Organic–Inorganic Framework, a Perovskite Layered Phosphonate MnO3PC6H4‐m‐Br⋅H2O. (18th June 2019) - Basu, Tathamay; Bloyet, Clarisse; Beaubras, Félicien; Caignaert, Vincent; Perez, Olivier; Rueff, Jean‐Michel; Pautrat, Alain; Raveau, Bernard; Lohier, Jean‐François; Jaffrès, Paul‐Alain; Couthon, Hélène; Rogez, Guillaume; et al.
Abstract: Very few hybrid organic–inorganic framework (HOIF) exhibit direct coupling between spins and dipoles and are also restricted to a particular COOH‐based system. It is shown how one can design a hybrid system to obtain such coupling based on the rational design of the organic ligands. The layered phosphonate, MnO3 PC6 H5 ⋅H2 O, consisting of perovskite layers stacked with organic phenyl layers, is used as a starting potential candidate. To introduce dipole moment, a closely related metal phosphonate, MnO3 PC6 H4 ‐ m ‐Br⋅H2 O is designed. For this purpose, this phosphonate is prepared from 3‐bromophenylphosphonic acid that features one electronegative bromine atom directly attached on the aromatic ring in the meta position, lowering the symmetry of precursor itself. Thus, bromobenzene moieties in MnO3 PC6 H4 ‐ m ‐Br⋅H2 O induce a finite dipole moment. This new designed compound exhibits complex magnetism, as observed in layered alkyl chains MnO3 PC n H2 n +1 ⋅H2 O materials, namely, 2D magnetic ordering ≈20 K followed by weak ferromagnetic ordering below 12 K ( T 1 ) with a magnetic field ( H )‐induced transition ≈25 kOe below T 1 . All these magnetic features are exactly captured in the T and H ‐dependent dielectric constant, ε′( T ) and ε′( H ). This demonstrates direct magnetodielectric coupling in this designed hybrid and yields a new path to tune multiferroic ordering and magnetodielectric coupling. Abstract : Direct magnetodielectric coupling is induced by introducing finite dipole moments in the organic layers of a 2D magnetic metal‐organic framework. This designed hybrid organic–inorganic framework MnO3 PC6 H4 Br⋅H2 O yields a new path to tune multiferroic ordering and magnetoelectric coupling.